Slouching towards a mass system : society, government and institutions in the United Kingdom - Fulton, Oliver [Verfasser] (My University, 1991)
"The paper describes and analyses postwar changes in regulatory and classificatory relationships between British governments and higher education institutions, in the context of broad social, economic and political change, in three time periods. The first, from 1945 to 1970, was marked by consolidation, increased government support, growth in numbers of institutions and students and a broad consensus around the desirability of expansion. The second, from 1970 to 1987, was marked by political hostility and, until 1983, stagnation in the rates of demand for places by students and for graduates by employers. The third period, from 1987 to the present day, suggests that Britain is now committing itself, whether deliberately or not, to a system of mass higher education, with a series of radical changes in government-higher education relationships. In conclusion the paper discusses alternative theoretical approaches to interpreting these developments: Trow's typology of elite-mass- universal higher education and its implications for transition between types; Teichler's analysis of models of higher education structure; and a possible synthesis between the two. But all such models need to pay due attention to the internal processes of higher education at the level of departmental and even individual behavior." (author's abstract) ((en)) Der Aufsatz beschreibt und analysiert die Entwicklung des Hochschulsystems in Grossbritannien von 1945 bis 1990 im Zusammenhang mit dem sozialen, wirtschaftlichen und politischen Wandel. Dabei wird vor allem das Verhältnis zwischen jeweiligen Regierungen und Hochschulinstitutionen untersucht, das durch Expansion und Massenuniversität einschneidende Veränderungen erfährt. Abschliessend werden verschiedene theoretische Ansätze zur Erklärung dieser Entwicklungen diskutiert. (IAB)
Der Abstieg zu einem Massensystem. Gesellschaft, Regierung und Institutionen im Vereinigten Königreich
Keywords: G 2.3.5 Wirtschaftsstrukturwandel; P 1.9 Begabte; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 2.3 Berufsbildungspolitik; Hochschulsystem; Entwicklung; Hochschulpolitik; Hochschulreform; Sozialer Wandel; Wirtschaftsstruktur; Strukturwandel; Elite; Bildungsexpansion; Quantitative Angaben